DISEMINASI BERBAGAI PRODUK OLAHAN LIMBAH KEPADA MASYARAKAT DESA SUMBER HARAPAN - Oktavia Nurmawaty Sigiro; Ega Aprisa; Uray Shelli; Noviyanti; Angga Saputra (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Waste is the residue from a process that is not used. If waste is allowed to accumulate, it will pollute the environment. Plant wastes such as coconut husk, rubber seeds and bagasse are often found in Sambas District. Coconut husk is the unused part of the coconut fruit, while the rubber seeds are not used because it is believed by the community to be toxic, and bagasse is sugarcane waste after the milling process. The purpose of this dissemination is to increase knowledge about waste management, especially coconut fiber, rubber seeds. The approach used in this activity includes a model of material presentation and discussion. This activity takes place in May 2022. This activity also motivates the people in Sumber Harapan Village to utilize the waste that is around them. It is hoped that this dissemination can make people aware of the importance of reducing waste in the environment so that it can be used as a product that provides added value so that it can improve the economy in Sumber Harapan Village.